(untitled) (A Luz em Cena: Revista de Pedagogias e Poéticas Cenográficas, 2025)
In this article, we present research on silicone prosthetics developed at the Universidade Federal do Estado do Rio de Janeiro’s Laboratório de Caracterização e Adereços. The study aims to assess and develop platinum-based silicone prostheses to improve realism and functionality in three distinct areas: performing arts, forensic medicine, and hospital simulation. The theoretical and practical studies involved visits to the simulation lab at the Escola de Enfermagem Alfredo Pinto (Unirio’s Nursing School), as well as discussions with forensic medicine professors. The practical development of the research included in-depth exploration of a variety of materials, sculpting techniques, and modeling and molding methods.